Association between cortical microinfarcts and total small vessel disease burden in cerebral amyloid angiopathy on 3‐Tesla magnetic resonance imaging. (27th November 2020) - Ii, Yuichiro; Ishikawa, Hidehiro; Shindo, Akihiro; Matsuyama, Hirofumi; Matsuura, Keita; Matsuda, Kana; Yoshimaru, Kimiko; Satoh, Masayuki; Kogue, Ryota; Umino, Maki; Maeda, Masayuki; Tomimoto, Hidekazu
Abstract: Background and purpose: Cortical microinfarcts (CMIs) are frequently found in the brains of patients with advanced cerebral amyloid angiopathy (CAA) at autopsy. The small vessel disease (SVD) score for CAA (i.e., the CAA‐SVD score) has been proposed to evaluate the severity of CAA‐associated vasculopathic changes by a combination of magnetic resonance imaging (MRI) markers. The aim of this study was to examine the association between total CAA‐SVD score and features of CMIs on in vivo 3‐Tesla MRI. Methods: Eighty patients with probable CAA were retrospectively analyzed. Lobar cerebral microbleeds, cortical superficial siderosis, enlargement of perivascular space in the centrum semiovale and white matter hyperintensity were collectively assessed, and the total CAA‐SVD score was calculated. The presence of CMI was also examined. Results: Of the 80 patients, 13 (16.25%) had CMIs. CMIs were detected more frequently in the parietal and occipital lobes. A positive correlation was found between total CAA‐SVD score and prevalence of CMI ( ρ = 0.943; p = 0.005). Total CAA‐SVD score was significantly higher in patients with CMIs than in those without ( p = 0.009). In a multivariable logistic regression analysis, the presence of CMIs was significantly associated with total CAA‐SVD score (odds ratio 2.318 [95% confidence interval 1.228–4.376]; p = 0.01, per each additional point). Conclusions: The presence of CMIs with a high CAA‐SVD score could be an indicator of more severe amyloid‐associated vasculopathic changes in patients with probable CAA. Abstract : Cortical microinfarcts detected on 3‐Tesla magnetic resonance imaging as hyperintense on (a) three‐dimensional (3D) double inversion recovery and(b) 3D fluid attenuated inversion recovery images, and hypointense on (c) 3D T1‐weighted imaging (arrows).